2022
DOI: 10.1111/joa.13661
|View full text |Cite
|
Sign up to set email alerts
|

Internal vascular channel architecture in human auditory ossicles

Abstract: The auditory ossicles play an essential role in sound transmission, and damage to them leads to conductive hearing loss. The predisposition of certain parts of the human ossicular chain to erosion is taken to be due to the pattern of blood supply, the long process of the incus being especially vulnerable (Gerlinger et al., 2009;Lindeman, 1964). Hamberger and Wersäll (1964) found that the internal channels in this process can be 'extremely thin,' especially where there had been previous infections, and linked a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Another factor that may also play a role in the degenerative abnormalities we found in our cases may be explained by changes to the blood supply to the ossicular chain. Manoharan et al 25 demonstrated that the distribution of blood flow is different in the malleus, incus, and stapes. As a known cause of peripheral vascular disease, it is possible that DM might also result in ischemic lesion to the ossicles and the ossicular joints contributing to these changes.…”
Section: Discussionmentioning
confidence: 99%
“…Another factor that may also play a role in the degenerative abnormalities we found in our cases may be explained by changes to the blood supply to the ossicular chain. Manoharan et al 25 demonstrated that the distribution of blood flow is different in the malleus, incus, and stapes. As a known cause of peripheral vascular disease, it is possible that DM might also result in ischemic lesion to the ossicles and the ossicular joints contributing to these changes.…”
Section: Discussionmentioning
confidence: 99%
“…We visually examined the vasculature in the 3D renderings. Based on the classi cation of vessels provided by Manoharan et al 24 , samples 1 and 2 appear to have a normal range of vascular channels. In contrast, sample 3 has a below-average number of vessels.…”
Section: Volume and Porosity Analysismentioning
confidence: 99%